Different coloured stones assembled to form the jagati (raised platform) - Temples of India Project Team (Jio Institute, 2024)
Debris from the original temple was salvaged when the current temple was reconstructed in the 1940s. These have been assembled in parts to form the jagati (raised platform). Different coloured stones are assembled here, some in pink sandstone and the rest in grey sandstone. However, it is not known where they were located in the original temple or if they came from multiple structures. The pink sandstone has floral designs with Stupa (dome-shaped memorials, made on the holy relics of the Buddha) motifs. The grey sandstone has the padma (lotus), the purna ghata (overflowing pot of prosperity) and the kalpa lata (creeper) motifs. The God of fire, Agni, is visible in the background (top), placed in the southeast corner of the garbhagriha as a dikpala (guardian of directions) of the southeast direction.